Modelling Malaysia flora multimedia presentation using object oriented database management system / Nora Muhammad Abdul Ghani - Muhammad Abdul Ghani, Nora (2007)
Multimedia information can be presented in the Object-Oriented Database Management System (OODBMS) which has the capability to handle complex data that Relational Database Management Systems (RDBMS) is not able to support. It is because in OODBMS, data types can be extended to support complex data. The objectives for this research are to investigate the data requirement for flora presentation, to design flora logical model using Object Oriented Database and to demonstrate the prototype of flora multimedia presentation. A lecturer in the Faculty of Applied Sciences Universiti Teknologi MARA was interviewed that flora database is interesting to present in interactive way rather than static presentation. Questionnaires were distributed to students at the Faculty of Applied Sciences Universiti Teknologi MARA to identify the multimedia requirements for the flora database. Subsequently, an interview was carried out with a lecturer from the same faculty to get the flora database requirements. Based on these requirements the logical model for the database was designed and a prototype was developed. The prototype was presented in interactive multimedia features which consist of video, image, audio and text. Thus, the multimedia prototype designed meets the requirements as stipulated by the users.